2015
DOI: 10.1186/s12886-015-0033-z
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal aflibercept (Eylea) injection for cystoid macular edema secondary to retinitis pigmentosa - a first case report and short review of the literature

Abstract: BackgroundCystoid macular edema (CME) in retinitis pigmentosa (RP) has been managed in several ways as documented in the literature, with little success, though. The aim of our study was to report for the first time in literature the use of aflibercept in a patient with RP and CME.Case presentationA 52-year-old man presented for blurred vision in his right eye. Best-corrected visual acuity (BCVA) was 3/10 in his right eye and 7/10 in his left eye. Physical examination and appropriate laboratory tests lead to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Improvement of CMT and VA following a single unilateral intravitreal injection of aflibercept (Eylea; Regeneron Pharmaceuticals, Tarrytown, New York, USA and Bayer Healthcare Pharmaceuticals, Berlin, Germany) in a patient aged 52 years with RP-CMO was observed and maintained at 6 months 84. We have observed similar responses85 and have commenced a prospective study to determine safety and efficacy of intravitreal aflibercept in RP-CMO (ClinicalTrials.gov identifier NCT02661711).…”
Section: Avenues Of Interventionmentioning
confidence: 89%
“…Improvement of CMT and VA following a single unilateral intravitreal injection of aflibercept (Eylea; Regeneron Pharmaceuticals, Tarrytown, New York, USA and Bayer Healthcare Pharmaceuticals, Berlin, Germany) in a patient aged 52 years with RP-CMO was observed and maintained at 6 months 84. We have observed similar responses85 and have commenced a prospective study to determine safety and efficacy of intravitreal aflibercept in RP-CMO (ClinicalTrials.gov identifier NCT02661711).…”
Section: Avenues Of Interventionmentioning
confidence: 89%
“…In a clinical study, the results indicated that an intravitreal aflibercept injection was an effective treatment for addressing macular edema in RP patients [88]. However, the level of VEGF was unknown in RP.…”
Section: Macular Abnormalitiesmentioning
confidence: 99%
“…This limitation of treatment could be explained by irreparable functional impairment within the fovea, arising from either chronic macular edema or photoreceptor cell dysfunction. Moustafa and Moschos [17] reported only 10% improvement in BCVA after the treatment, despite the significant resolution of macular edema in OCT scan. They deem that reasonable explanation is that CME is only one factor that affects the vision, while atrophy of the retina (particularly of the photoreceptors) also has impact on the visual function.…”
Section: Discussionmentioning
confidence: 96%
“…The responses to the treatment seem to be individually variable. There are several therapeutic approaches for CME in RP, such as systemic or intravitreal corticosteroids, grid laser photocoagulation, systemic or topical carbonic anhydrase inhibitors [9], and in the recent years some authors found the inhibitors of the vascular endothelial growth factor (VEGF) to be effective [17]. In any case, many practitioners believe that carbonic anhydrase inhibitors are the mainstay of treatment [9].…”
Section: Discussionmentioning
confidence: 99%